Measurement of cosmic-ray muons with the Distributed Electronic Cosmic-ray Observatory, a network of smartphones. (13th April 2016) - Vandenbroucke, J.; BenZvi, S.; Bravo, S.; Jensen, K.; Karn, P.; Meehan, M.; Peacock, J.; Plewa, M.; Ruggles, T.; Santander, M.; Schultz, D.; Simons, A.L.; et al.
Abstract: Solid-state camera image sensors can be used to detect ionizing radiation in addition to optical photons. We describe the Distributed Electronic Cosmic-ray Observatory (DECO), an app and associated public database that enables a network of consumer devices to detect cosmic rays and other ionizing radiation. In addition to terrestrial background radiation, cosmic-ray muon candidate events are detected as long, straight tracks passing through multiple pixels. The distribution of track lengths can be related to the thickness of the active (depleted) region of the camera image sensor through the known angular distribution of muons at sea level. We use a sample of candidate muon events detected by DECO to measure the thickness of the depletion region of the camera image sensor in a particular consumer smartphone model, the HTC Wildfire S. The track length distribution is fit better by a cosmic-ray muon angular distribution than an isotropic distribution, demonstrating that DECO can detect and identify cosmic-ray muons despite a background of other particle detections. Using the cosmic-ray distribution, we measure the depletion thickness to be 26.3 ± 1.4 μ m. With additional data, the same method can be applied to additional models of image sensor. Once measured, the thickness can be used to convert track length to incident polar angle on a per-event basis. Combined with a determination of the incident azimuthal angle directly from the track orientation in the sensor plane, this enables direction reconstruction of individual cosmic-ray events using a single consumer device. The results simultaneously validate the use of cell phone camera image sensors as cosmic-ray muon detectors and provide a measurement of a parameter of camera image sensor performance which is not otherwise publicly available.